Local electrical properties of PTB7 film - Yedrissov, A.; Alekseev, A.; Ilyassov, B. (ELSEVIER SCIENCE BV, 2017)
A study of the spreading of currents and current-voltage characteristics in a pure PTB7 thin film by atomic force microscopy (AFM) technique was carried out in order to investigate the processes of transport of positive charge carriers in the nanoscale range. It was showed that the numerical values of the carrier mobility can significantly differ on the nanoscale and require correct interpretation of processes with the scale that are comparable with the morphological features of organic solar cells. © 2017 Elsevier Ltd. All rights reserved. Selection and Peer-review under responsibility of 4th International Conference on Nanomaterials and Advanced Energy Storage Systems (INESS 2016).
Keywords: Organic photovoltaic solar cells; PTB7; the mobility of the charge carriers